THE EFFECT OF A FOCUS GROUP DISCUSSION–BASED NUTRITION EDUCATION MODULE ON CHANGES IN NUTRITIONAL KNOWLEDGE AMONG FAMILY ASSISTANCE TEAM MEMBERS IN STUNTING PREVENTION - Jelita Sahetapy; Warda Anil Masyayih; Istiadah Fatmawati (PRIMA WIYATA HEALTH, 2026)
Background: Stunting remains a major public health challenge in Indonesia, requiring active involvement of community-based human resources, including Family Assistance Teams (FATs), in supporting families at risk. However, limited nutritional knowledge among FAT members may reduce the effectiveness of stunting prevention efforts. Objective: This study aimed to examine changes in nutritional knowledge among FAT members following the implementation of a nutrition education module delivered through a Focus Group Discussion (FGD) approach. Methods: A quantitative pre-experimental study with a one-group pretest–posttest design was conducted. A total of 30 FAT members were selected using simple random sampling. Participants received a structured nutrition education module facilitated through FGD sessions. Nutritional knowledge was assessed before and after the intervention using a questionnaire. Data were analyzed using the Wilcoxon signed-rank test to evaluate differences in knowledge scores before and after the intervention. Result: The results demonstrated a statistically significant increase in nutritional knowledge scores following the FGD-based education module (p < 0.05), indicating a meaningful difference between pre-intervention and post-intervention measurements. Conclusion: The FGD-based nutrition education module was associated with improved nutritional knowledge among Family Assistance Team members. Nevertheless, given the absence of a control group, causal inferences should be interpreted with caution. Further studies employing controlled or experimental designs are recommended to confirm effectiveness and to assess the impact of improved knowledge on practical stunting prevention outcomes.